ILRAD 1992 annual report - International Laboratory for Research on Animal Diseases (1993)
This annual report outlines research and other activities of the International Laboratory for Research on Animal Diseases (ILRAD). The chapter deals with research on theileriosis and trypanosomiasis; studies on socio-economics; activities under the cooperative programs - training and information and the research support units. Topics of discussion include epidemiology; biology; diagnosis antigens and vaccine development; molecular genetics; host immune responses and genetics of host resistance.